2020
DOI: 10.1021/acs.jpcc.0c05713
|View full text |Cite
|
Sign up to set email alerts
|

New Data-Driven Interacting-Defect Model Describing Nanoscopic Grain Boundary Compositions in Ceramics

Abstract: A new data-driven interacting-defect model has quantitatively described the nanoscopic composition of high solute concentrations at grain boundaries in ion-conducting ceramics. The successful model is a data-driven Cahn-Hilliard methodology for interfaces and surfaces, introduced and demonstrated in this report. The model is applied to high spatial resolution composition data gathered at grain boundaries in calcium-doped ceria. The statistical methodology for the data-driven procedure shows definitively that g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Rather, it should be seen as an indicator of whether a Mott-Schottky model is applicable or not. Deviations caused by other influences, e. g. additional charge-carrier species, intrinsic structural resistances, 37 secondary phases 1,[27][28][29][30] or defect interactions, 39,61,89 could lead to similar inconsistencies.…”
Section: How Can Restricted Equilibrium and Mott-schottky Bementioning
confidence: 99%
“…Rather, it should be seen as an indicator of whether a Mott-Schottky model is applicable or not. Deviations caused by other influences, e. g. additional charge-carrier species, intrinsic structural resistances, 37 secondary phases 1,[27][28][29][30] or defect interactions, 39,61,89 could lead to similar inconsistencies.…”
Section: How Can Restricted Equilibrium and Mott-schottky Bementioning
confidence: 99%
“…In this case, the interactions between Y and oxygen vacancies govern segregation behavior by inducing a phase transition near the GB. Such characterization method capable of atomically mapping elements enables GB design at atomic scale, paving new avenues towards controlling and optimizing properties of oxides, particularly when supported by theoretical calculations such as Monte Carlo (MC), DFT, or phase field simulations [18,22,221].…”
Section: Chemical Analysis By Edxs and Eelsmentioning
confidence: 99%
“…Therefore, understanding the basics of interfaces is key in optimization of ceramics for a wide range of applications including electrochemical energy conversion and storage, optical, magnetic, and mechanical applications, thermal applications including thermal/environmental barrier coatings, refractories, etc. [5][6][7][18][19][20][21][22][23][24][25]. This effect becomes more significant in nanocrystalline ceramics with higher volume fractions of interfaces.…”
Section: Introduction 1background and Motivationmentioning
confidence: 99%
“…Crystalline defects (e.g., dislocations, homo- and hetero-interfaces) and other extended structural irregularities such as strain fields are shown to control cation anti-site and anion-Frenkel defect concentrations, and can also enhance pyrochlore phase-transformation kinetics under applied pressure ( Rittman et al, 2017b ) and irradiation in fluorites ( Schuster et al, 2009 ). Strain-induced structural distortions such as misfit dislocations, cation intermixing, and oxygen vacancies ( Bowman et al, 2015 ; Bowman et al, 2017 ; Perriot et al, 2017 ; Tong et al, 2020 ) commonly arise at interfaces and can lead to unique chemical, transport and radiation responses ( Haider et al, 1998 ; Gázquez et al, 2017 ; Lehmann et al, 2017 ; O’Quinn et al, 2017 ; Shamblin et al, 2018 ; Gussev et al, 2020 ). Heterointerface engineering of fluorites, perovskites and pyrochlores has been shown to control local oxygen diffusivity ( Schweiger et al, 2017 ), to affect local radiation response ( Spurgeon et al, 2020 ) and to produce novel topological phases ( Gallagher et al, 2016 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heterointerface engineering of fluorites, perovskites and pyrochlores has been shown to control local oxygen diffusivity ( Schweiger et al, 2017 ), to affect local radiation response ( Spurgeon et al, 2020 ) and to produce novel topological phases ( Gallagher et al, 2016 ; Li et al, 2021 ). Other types of extended crystalline defects, such as dislocations ( Sheth et al, 2016 ; Shafieizadeh et al, 2018 ) and grain boundaries ( Bowman et al, 2015 ; Bowman et al, 2017 ; Perriot et al, 2017 ; Gupta et al, 2020 ; Syed et al, 2020 ; Tong et al, 2020 ) have been shown to behave as fast oxygen transport pathways in some cases. Even small, localized, atomic displacements such as local changes in bonding environment (e.g., coordination), polyhedral distortions (e.g., bond length or angle), polyhedral tilting and the adoption of short-range polyhedral configurations or ‘structural motifs’ ( Shamblin et al, 2016 ; Sun et al, 2016 ) can affect functional properties.…”
Section: Introductionmentioning
confidence: 99%